Music genre classification with convolutional neural network - Chowdhury, Masud; Tilok, Ibnul Islam; Das, Prodipta; Chowdhury, Avoy; Anas, MD. Abdullah Al Masum (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.